The Relationships of Markers of Cholesterol Homeostasis with Carotid Intima-Media Thickness - Weingärtner, Oliver (Public Library of Science, 2010)
BACKGROUND: The relationship of cholesterol homeostasis and carotid intima-media thickness (cIMT) is unknown. To address this, we assessed markers of cholesterol homeostasis (serum plant sterols and cholesterol precursor concentrations as surrogate measures of cholesterol absorption and synthesis, respectively) and cIMT in a middle-aged, statin-naive population. METHODS: In this prospective study of primary prevention cIMT was measured by ultrasound in 583 hospital employees aged 25–60 years without prevalent cardiovascular disease or lipid-modifying medication. The serum concentrations of plant sterols (as markers of cholesterol absorption) were measured by gas-liquid chromatography. Lathosterol serum concentrations were quantitated to assess hepatic cholesterol synthesis. RESULTS: cIMT correlated positively with serum cholesterol (r = 0.22, P<0.0005) and lathosterol-to-cholesterol (r = 0.18, P<0.001). In contrast, plant sterols, as markers of cholesterol absorption, showed a weak negative correlation to cIMT measurements (r = −0.18; P<0.001 for campesterol-to-cholesterol). Stratifying subjects by serum sterol levels, we found that cIMT increased continuously over quintiles of serum cholesterol (P<0.0005) and was positively associated to serum lathosterol-to-cholesterol levels (P = 0.007), on the other hand, plant sterol levels showed a weak negative association to cIMT (P<0.001 for campesterol-to-cholesterol). CONCLUSIONS: In this population without prevalent cardiovascular diseases or lipid-modifying medication, markers of increased endogenous cholesterol synthesis correlated positively with cIMT, while markers of cholesterol absorption showed a weakly negative correlation. These data suggest that not only total serum cholesterol levels but also differences in cholesterol homeostasis are associated with cIMT.